Validation and sensitivity study of Micro-SWIFT SPRAY against wind tunnel experiments for small-scale air dispersion modeling between mountains and dense building at a nuclear power plant site. (December 2021) - Dong, Xinwen; Zhuang, Shuhan; Fang, Sheng; Li, Xinpeng; Wang, Shuntan; Li, Hong; Cao, Jianzhu
Abstract: The small-scale air dispersion modeling around nuclear power plants is important for emergency planning and response of the emerging small modular reactors. But it is often challenging, because of the dense buildings and different topographies. Micro-SWIFT SPRAY (MSS) provides a potential solution, because it can calculate the 3D wind and concentration fields with building effects in an acceptable time for emergency response. However, the corresponding validation hasn't been demonstrated adequately. In this study, MSS is systematically evaluated against two wind tunnel experiments for small-scale air dispersion modeling at a nuclear powerplant site with irregular building layout and different topographies, including the 2D horizontal and vertical observations of the wind direction, wind speed and concentration. Sensitivity studies are performed concerning the particle number, the horizontal and vertical grid sizes. The results demonstrate that MSS can reproduce the ground-level wind and concentration among buildings with acceptable accuracy. For concentration, the fraction of simulations within a factor of two/five exceeds 79.0% and 90.9% respectively. The computation time can be reduced to 24 min with acceptable metrics. The artificial high concentrations and zero-valued simulations at high attitude places were observed, which can be avoided by using an appropriate grid size while maintaining simulation details. Highlights: Horizontal and vertical validations of wind and concentration in a densely built area. The wind matches observations among the dense buildings, but the details are limited. MSS shows better performances in the presence of dense downwind buildings. MSS may show overestimations between downwind buildings taller than the release. Appropriate grid size may avoid the overestimation and improve vertical profiles.